Desempenho de um motor diesel de injeção indireta em função da variação do teor de biodiesel - Sala, José Antonio (2008)
Due to the current world scenery of energy, the biodiesel presents a great potential as option to consumption of fuels of the finite sources. The largest use of the biodiesel in the world is with the methyl ester of soybean oil, due to the production scale. In general its use happens in form of blends with diesel oil in different rates. This work of research shows the influence of different levels of biodiesel blends and diesel oil. They were tested using a dynamometer hydraulic bench for evaluation of a diesel engine of 4 times with indirect injection, naturally aspirated. The fuels used were obtained by blends of soy bean methyl ester oil with conventional diesel with levels ranging from 5% to 100% biodiesel. I t hás been compared to the results obtained by different mixes with the B2 diesel oil, with no changes or adjustments in the engine. The best results of speci fic consumption were reached with blends up to 20% of biodiesel, otherwise tenors above 50% present médium consumption up to 7,2% larger than the convent ional diesel. The torque showed a declining while the ve getable fuel concentration was increased, which the worst result was present by B100 that had lost 6,8% compared to the testifier trial. The noxious exhaust ion gasses, to the environment, have the emi ssion decreased with the introduction of the biodiesel, except the NOx that presents rise when the levels of the added biodiesel are superior to 20%. The results suggest that largers tenors than 20% in the mixture (B20) demand modifications or adjustments in the motor for a better performance.